EFFECTIVENESS OF INQUIRY-BASED LEARNING TOWARDS MASTERING THE CONCEPT OF UNSATURATED HYDROCARBONS IN UNDERGRADUATE STUDENTS - Helda Lupita Septyastuti; Sutrisno Sutrisno; Hayuni Retno Widarti (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
Inquiry learning can be applied to chemistry learning at any level of education. This is according to the characteristics of chemistry, which is based on empirical evidence for real-world study. One of the topics studied in Organic Chemistry Lecture is an unsaturated hydrocarbon that discussed the structure, nomenclature, properties, manufacture, and usability. There are various models or strategies of inquiry for chemistry learning, especially guided inquiry. One of the guided inquiry-based chemistry learning strategy innovations is the OE3R (Orientation - Exploration - Explanation - Elaboration - Reflection) strategy for various education levels, high schools, and universities. This research aimed to determine the effectiveness of guided inquiry-based learning with OE3R strategy in undergraduate students' conceptual understanding of the Unsaturated Hydrocarbon concept. The research using a Quasi Experiment with a pretest-posttest control group design. Conceptual understanding with OE3R Strategy proven to be better than Expository Strategy. This can be seen from achieving minimum completeness criteria, which is 92.3% for OE3R and 72.2% for expository. It can also be seen from the N-gain value for the OE3R Strategy (0.43), which is significantly better than the Expository Strategy (0.27).